Exploring Nexus between food security and the loss of agro-biodiversity: a study in Madhya Nepal, Lamjung - Binita Shahi; Shudarshan Hamal; Leela Raj Upadhyay (Discover Applied Sciences)
Abstract Nepal has made significant strides in enhancing food security, achieving a moderate hunger index of 15.0 in 2023. However, the relationship between food security and reduced agro-biodiversity remains underexplored. This study investigates this interplay in Madhya Nepal Municipality, Lamjung District, Gandaki Province. Using Food Consumption Score (FCS) and Reduced Coping Strategies Index (rCSI), the study assesses food availability, nutrition sources, and coping mechanisms. The methodology includes field surveys, interviews, and analysis of 30 years of climate data. Ward-wise investigations reveal challenges and opportunities through quantitative and qualitative approaches. Motivated by the complex dynamics affecting food security and agricultural practices amid evolving environmental conditions, this research highlights community struggles and opportunities. It emphasizes the need for a balance between traditional and hybrid agriculture, calling for adaptive strategies to address climate change impacts. Integrating traditional knowledge with scientific innovations is crucial for sustainable food production. Results show higher food stock in some wards due to drought-resistant crops, while others face challenges with traditional farming reliance. Climate data analysis indicates significant temperature increases, affecting rice adaptation and traditional practices. Increased adoption of hybrid crops, supported by irrigation and improved technical knowledge, boosts cereal productivity. The study concludes a positive correlation between agro-biodiversity and food security, highlighting diverse agricultural systems' importance in mitigating climate change challenges.